Serial lipectomy and liposuction for management of Madelung syndrome: About a case - SILVA, PEDRO HENRIQUE DE ARAÚJO; SÁ, JAIRO ZACCHÊ DE; MOTTA, FLÁVIO JOSÉ TEIXEIRA ROCHA ATAÍDE DA; CASTRO, HELENA GABRIELE ALVES; AMORIM, VINICYUS EDUARDO MELO; VIANA, ANDRESA DOS SANTOS; BRAVIN, LARISSA CARARETO; PONTUAL, PEDRO HENRIQUE (Revista Brasileira de Cirurgia Plástica (RBCP) – Brazilian Journal of Plastic Surgery, 2024)
Madelung’s disease is characterized by the symmetric and diffuse accumulation of adipose tissue with slow and progressive tumor growth. In this case report, a patient with this syndrome was treated at Hospital das Clínicas, in Recife, PE, to reduce the lipomatous content through a lipectomy. The patient presented large masses of elastic adipose tissue around the neck and supraclavicular region and the therapeutic proposal consisted of a two-stage surgery, with liposuction and anterior cervical lipectomy, followed by liposuction and posterior cervical lipectomy. Before surgery, a cardiological opinion was requested, which indicated an intermediate risk but did not contraindicate the procedure. Four days after surgery, the patient presented bruises and peripheral edema in the cervical surgical wound but was asymptomatic. Lipectomy and liposuction techniques are considered the most effective treatment methods for Madelung disease. However, the choice of surgery should be based on a comprehensive assessment of the severity of the disease, location of the mass, and patient expectations, as both techniques have advantages and disadvantages.
Keywords: Lipectomy; Lipoma; Neck; Plastic surgery procedures; Lipomatosis, multiple symmetrical